1º Encontro de Arqueologia do Algarve - Rocha, Leonor (2010)
In the following paper the results of two emergency excavations undertaken by the department of Silves in recente years are presented. The first intervention took place in 1999 at Praia do Forte Novo (Quarteira, Loulé). At this site a Neolithic settlement was confirmed by the presence of many ceramic materials dating to that period. The second intervention was undertaken at the city of Silves (Rua de Acesso ao Castelo) in 2000. Here an ossuary area was identified.